Prediction of renal function improvement in azotemic patients using glomerular filtration rate from 99mTc-DTPA renal scan: An observational study. Issue 51 (23rd December 2021) - Yu, Hoon; Kim, Hyosang; Shin, Hyung Soo; Lee, Hyo Sang
Abstract : Abstract: This study aimed to evaluate the ratio of glomerular filtration rate (GFR) from 99m Tc-diethylenetriamine-pentaacetic acid dynamic renal scan (GFRSCAN ) to estimated GFR (eGFR) as a predictor of renal function improvement in patients with azotemia. A retrospective review of medical records was conducted to identify consecutive patients with newly discovered or aggravated azotemia who underwent 99m Tc-diethylenetriamine-pentaacetic acid renal scan. Significant renal function improvement was defined as ≥100% and ≥10 mL/min improvement of eGFR at 12 weeks compared to eGFR on the day of renal scan (eGFR0 ). The GFRSCAN /eGFR0 ratio was evaluated as a predictor of significant renal function improvement using logistic regression and receiver operating characteristic (ROC) curve analyses. Added value of the GFRSCAN /eGFR0 ratio in the prediction of significant renal function improvement were demonstrated by adjusting for best clinical predictor variables. The eligibility criteria were met by 224 patients, among whom 22 patients (9.8%) showed significant renal function improvement. The odds ratios of the GFRSCAN /eGFR0 ratio for predicting significant renal function improvement were 1.76 (95% confidence interval [CI]: 1.26–2.45, P  < .001) in the univariable analysis and 1.70 (95% CI: 1.19–2.42, P  = .003) after adjusting for clinical variables. The area under the ROC curve of the GFRSCAN /eGFR0 ratio for predicting significant renal function improvement was 0.762 (95% CI: 0.648–0.871). The addition of the GFRSCAN /eGFR0 ratio to the best clinical prediction model raised the area under the ROC curve from 0.726 to 0.794, and this increment was statistically significant ( P  = .02). The GFRSCAN /eGFR ratio can predict renal function improvement in patients with azotemia. Future prospective studies are necessary to validate its potential clinical utilities.